The Growth and Yield of Sweet Corn with Herbicide Application on Ultisol - Nguyen Thi, Tho; Agustian, Agustian (Jurnal Solum, 2023)
Glyphosate is a widely used herbicide in the world, including in Indonesia. Many studies have reported that the use of glyphosate is harmful to soil microorganisms and, few reports on the effect of glyphosate on the growth and yield of corn. This study investigated the growth and yield of sweet corn cultivated on Ultisols under the effect of Glyphosate application. This study used a completely randomized design with four treatments and three replications in the greenhouse from July to November 2022. The treatments were the volume of herbicide consisting of 0, 5, 6, and 7 L/ha (equivalent 0, 2.43, 2.91, 3.4 Kg glyphosate-isopropyl ammonium/ha). The height of corn with the treatment 5 L/ha before 50 DAS got the highest value among all treatments with statistical differences. The 5 L/ha treatment also gave the best weight on corncob and corn roots at harvest time. The yield in the treatment 5 L/ha was 8.72 tons/ha, which was higher than the other treatments with no herbicide application, 6 L/ha and 7 L/ha, that gave 7.82, 6.89, and 6.33 tons/ha, respectively. From the results of this study, we can conclude that glyphosate affects the yield of sweet corn, which tends to decrease when glyphosate is used more than 6 L/ha.